2021
DOI: 10.1186/s12903-021-02028-7
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram based on clinical characteristics and serological inflammation markers to predict overall survival of oral tongue squamous cell carcinoma patient after surgery

Abstract: Background Oral tongue squamous cell carcinoma (OTSCC) is a prevalent malignant disease that is characterized by high rates of metastasis and postoperative recurrence. The aim of this study was to establish a nomogram to predict the outcome of OTSCC patients after surgery. Methods We retrospectively analyzed 169 OTSCC patients who underwent treatments in the Cancer Hospital of Shantou University Medical College from 2008 to 2019. The Cox regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 58 publications
(51 reference statements)
1
11
0
Order By: Relevance
“…The VSA and the FCR are two comprehensive parameters reflecting the range of tongue movement [ 35 ]. Currently, the demand for noninvasive screening tests, such as tissue fluorescence imaging [ 37 ], salivary metabolomics [ 38 ], and serological markers [ 39 ], has greatly increased [ 40 ]. Our previous study found that the FCR could be a potential acoustic marker for detecting speech disorders in patients with TSCC [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The VSA and the FCR are two comprehensive parameters reflecting the range of tongue movement [ 35 ]. Currently, the demand for noninvasive screening tests, such as tissue fluorescence imaging [ 37 ], salivary metabolomics [ 38 ], and serological markers [ 39 ], has greatly increased [ 40 ]. Our previous study found that the FCR could be a potential acoustic marker for detecting speech disorders in patients with TSCC [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A nomogram utilizes MLR to combine multiple features linearly, thus predicting the disease status and treatment outcomes. For example, a combination of clinical characteristics and serum inflammation markers has been developed to predict overall survival in OSCC patients [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of multivariate analysis in the training cohort, we finally included tumor site, grade, AJCC T stage, number of PLNs and LNR into the nomogram for OS. Although the prognostic significance of tumor site, grade, and AJCC T stage have been reported and presented in the manner of nomogram previously [ 19 , 20 , 23 , [32] , [33] , [34] ], our nomogram is the first one that we are aware of to incorporate LNR into the prognostic model. Another notable hallmark of our nomogram is the inclusion of PLNs.…”
Section: Discussionmentioning
confidence: 99%